Causes and effects of social media engagement in luxury fashion marketing: A comparative study over the COVID pandemic - Jiayi Huang; Peng Zhou (Cardiff University, Cardiff Business School, 2024)
This paper examines cross-country heterogeneities and over-time changes of the role of social media marketing (SMM) in the luxury fashion industry. A comprehensive literature review is conducted on customer value, purchase intention, and engagement motivation to understand the causes and effects of SMM. Based on the survey data in China and the UK, probit and oprobit regressions are employed to estimate the models of SMM. Results show that affectional and cognitive motives are the two primary drivers of SMM engagement in both countries. Chinese customers are more susceptible to SMM than British counterparts, suggesting significant potential benefits of developing SMM strategies in China. Over time, SMM has become an irreversible trend of luxury brand management after the COVID pandemic. Identified heterogeneities and changes call for differentiated international marketing strategies in different countries at different times.
Keywords: 330; Social Media; Brand Interaction; Luxury Fashion Marketing